Erratum to: Circular Economy in Indonesian MSMEs: A Qualitative Study on The Role of Eco-Innovation and Sustainable Supply Chains - JABM Editorial (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Correction to: Mekaniwati, A., Munawar, A., Rainanto, B. H., & Maulina, D. (2026). Circular economy in Indonesian MSMEs: A qualitative study on the role of eco- innovation and sustainable supply chains. Jurnal Aplikasi Bisnis Dan Manajemen (JABM), 12(1), 352–363. https://doi.org/http://dx.doi.org/10.17358/jabm.12.1.352. An error appeared in the article entitled “Circular Economy in Indonesian MSMEs: A Qualitative Study on the Role of Eco-Innovation and Sustainable Supply Chains” published in Jurnal Aplikasi Bisnis dan Manajemen (JABM). In the published article, several editorial errors were identified, including a duplicated sentence in the Results and Discussion section and inconsistency in the capitalization format of article titles in the References section. The corrections are as follows: Corrections on pages 358–359: Page 358 (Column 2) and Page 359 (Column 1): A duplicated sentence appeared in two consecutive paragraphs: "At the economic level, as shown in the heatmap, MSMEs have successfully transformed waste into value-added products such as ecobricks and recycled paper. One MSME owner in Bogor confirmed this by stating that handicraft bags made from plastic waste can increase the income of local housewives." The duplicated sentence on page 359 should be removed to maintain the logical flow of the discussion. Corrections on pages 362–363 (References): The capitalization format of several article and book titles in the References section was inconsistent. All titles have been revised to follow Sentence Case in accordance with the APA Style (7th Edition) guidelines. Examples of the corrections are as follows: Linking Urbanization and the Environment: Conceptual and Empirical Advances, Should be: Linking urbanization and the environment: Conceptual and empirical advances Qualitative Inquiry and Research Design Choosing among Five Approaches, Should be: Qualitative inquiry and research design: Choosing among five approaches The original article can be access online at: http://dx.doi.org/10.17358/jabm.12.1.352